Knowledge dialogues for better health: complementarities between health innovation studies and health disciplines. (1st March 2020) - Natera, José Miguel; Rojas, Soledad; Dutrénit, Gabriela; Vera-Cruz, Alexandre O.
Abstract : Health innovation studies and the health disciplines highlight the importance of using knowledge to improve human welfare. However, these disciplines rarely yield discussion about this issue. The objective of this paper is to establish a dialogue between health innovation studies and the health disciplines, and to reveal the complementarities between these approaches. We present a revision of selected models of health knowledge use. From health innovation studies, we consider two models focused on the nature of health innovation, and two others that orient health innovation studies towards addressing inclusive development issues. From the health disciplines, we analyse translational research and knowledge translation models. Using a systemic perspective, we structure our analysis of complementarities on four analytical dimensions: (i) The actors, proposing the recognition of the public sector, the productive sector, the scientific community, and health services providers. We also define two dynamic actors: knowledge users and knowledge beneficiaries. (ii) The interactions, considering them as asymmetrical to facilitate knowledge flows. (iii) The process, based on specific models of healthcare activities and a broad set of validation mechanisms (not only market-related). (iv) The institutional framework, proposing consideration of formal institutions (e.g. regulations) and informal institutions (e.g. socio-cultural background).